Pengujian racun perut ekstrak aseton tanaman putri malu (Mimosa pudica L.) untuk mengendalikan hama Spodoptera frugiperda: Evaluation of the ingestion toxicity of acetone extract of Mimosa pudica L. against Spodoptera frugiperda - Dewi Wulan Sari (COMPOSITE : Jurnal Ilmu Pertanian, 2026)
Maize (Zea mays L.) is one of the major agricultural commodities that contributes significantly to national food security and economic development. However, maize production is constrained by infestations of the fall armyworm (Spodoptera frugiperda), a destructive pest capable of causing substantial yield losses. Botanical pesticides have emerged as an environmentally friendly alternative for managing this pest. This study aimed to evaluate the ingestion toxicity of acetone extract of Mimosa pudica L. against S. frugiperda. The experiment was conducted at the Plant Pest and Disease Laboratory, Faculty of Agriculture, Universitas Islam Sumatera Utara, from April 24 to October 15, 2022. A completely randomized design (CRD) with a single factor was applied, consisting of five treatments: control, 0.125%, 0.25%, 0.375%, and 0.5% acetone extract of M. pudica, each with five replications. Fresh M. pudica plants were extracted using acetone solvent, and the resulting extract was applied as an ingestion treatment to S. frugiperda larvae. The observed parameters included larval mortality, median lethal time (LT??), and median lethal concentration (LC??). The highest extract concentration (0.5%) resulted in 90% larval mortality, indicating a concentration-dependent increase in insecticidal activity. Lower concentrations produced reduced mortality rates, demonstrating that the efficacy of the extract increased with concentration. These findings indicate that acetone extract of M. pudica has considerable potential as a botanical insecticide for the sustainable management of S. frugiperda